POSSIBILITIES FOR ECHOCARDIOGRAPHIC DETERMINATION OF PULMONARY ARTERY PRESSURE IN PATIENTS WITH SYSTEMIC CONNECTIVE TISSUE DISEASES: DATA OF A RHEUMATOLOGY EXPERT CENTER - E. V. Nikolaeva; Yu. O. Korsakova; I. A. Kurmukov; S. I. Glukhova; N. N. Yudkina; A. V. Volkov (Научно-практическая ревматология, 2015)
Objective: to assess the significance of noninvasive estimation of pulmonary artery pressure (PAP) using Doppler echocardiography (echoCG) as compared to invasive measurements of this parameter in patients with systemic connective tissue diseases (SCTD). Subjects and methods. The invasively measured hemodynamic parameters versus those estimated at echoCG were analyzed. The analysis included 156 paired studies of 61 patients with pulmonary hypertension (PH) in the presence of SCTD and 26 patients, in whom PH was not verified by catheterization. Forty-five patients were found to have PH; PH was caused by left heart involvement in 7 patients and by hypoxemia in 9. Results and discussion. Systolic PAP (SPAP) measured by echoCG averaged 72.4±33.7 mm Hg and that by right heart catheterization did 63.3±25.1 mm Hg. The correlation of the values of this measure, which were obtained by the two methods, was highly significant (r = 0.83; p < 0.00001). Right atrial pressure (RAP) measured by echoCG and catheterization was 8.4±4.1 and 6.7±5.2 mm Hg, respectively. The echoCG and catheterization RAP correlation was highly significant (r = 0.57; p < 0.0001). Despite the high correlation coefficients, echoCG failed to detect higher SPAP in 7 patients with PH verified by catheterization; EchoCG could not detect higher SPAP; false-positive results were absent. EchoCG demonstrated good sensitivity (94%) and specificity (100%) for a threshold SPAP of 40.1 mm Hg (the area under the curve was 0.99 (p < 0.0001) with 95% CI 0.98–1.01. The echoCG determination of RAP by the existing methods showed good sensitivity (79%) and specificity (69%) for its threshold of 5 mm Hg (the area under the curve was 0.79 (p < 0.0001) with 95% CI 0.70–0.95. The patients with low level of mean PAP (PAPmean) measured by catheterization showed a difference of > 10 mm Hg as compared with the echoCG levels in 5% of the cases; > 20 mm Hg discrepancy was not noted. In patients with high PAPmean, the differences of > 10 and > 20 mm Hg were observed in 28.9 and 34.2% of the cases, respectively. Analysis of the Bland–Altman agreement showed deviations of +8.22 mm Hg for SPAP (95% CI 6.6–12.8) and +1.56 mm Hg for RAP (95% CI 0.85–2.27). The standard deviation of differences was 18.4 for SPAP and 4.5 for RAP. There was a relationship between the differences from their mean value, which is more significant for SPAP. The correlation coefficient for SPAP was 0.43 (p < 0.001) and that for RAP was 0.31 (p < 0.05). Thus, the Bland–Altman analysis revealed a systematic disparity, suggesting a weak agreement of the results of the two methods determining SPAP and RAP. Conclusion. Our investigation demonstrated that echoCG proved to be a valid and reliable screening method for PH in patients with SCTD. More accurate estimation of SPAP and RAP measurement requires the application of invasive diagnostic methods.